A novel immersive virtual environment setup for behavioural experiments in humans, tested on spatial memory for environmental spaces - Meilinger, T.; Riecke, B.E.; Berger, D.; Bülthoff, H.H. (Max-Planck-Institute for Biological Cybernetics, 2007)
We present a summary of the development of a new virtual reality setup for behavioural experiments in the area of spatial cognition. Most previous virtual reality setups can either not provide accurate body motion cues when participants are moving in a virtual environment, or participants are hindered by cables while walking in virtual environments with a head-mounted display (HMD). Our new setup solves these issues by providing a large, fully trackable walking space, in which a participant with a HMD can walk freely, without being tethered by cables. Two experiments on spatial memory are described, which tested this setup. The results suggest that environmental spaces traversed during wayfinding are memorised in a view-dependent way, i.e., in the local orientation they were experienced, and not with respect to a global reference direction.
Keywords: MPI-TR; Riecke; Riecke_2007; TR; bernhard-riecke; iSpaceWeb